Work Stress and Discipline On Employee Performance Mediated By OCB - Riyandi, Taufik; Johanes Lo, Singmin (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Objective – Examining regional red bank employees 2 researchers conducted a pre-survey of 2 key people, it was found that the problem of work stress and employee work discipline was the reduction in employee performance. This research was conducted on 179 employees in a unidirectional (one-sided) manner with a significance level of 0.05 or alpha of 5%. If the T-statistic value is > 1.64 and the P-value < 0.05 then the hypothesis results can be accepted. Hypothesis testing results with Boostraping using SmartPLS 3.2.9 software. Research discussions have proven that increasing work stress will reduce employee performance, even if it has to be mediated by OCB. mediation by OCB will improve employee performance. From this research it can be seen that the P-Value of the 7 hypotheses has a significant effect, but there are 2 hypotheses that show a significant negative effect, namely Hypothesis 2 and Hypothesis 6, which means that the more employee work stress increases, the more it will reduce employee performance, others are the same as which has a significant positive effect. Thus, for the Company to pay attention to the level of work stress and work discipline of its employees, they will get optimal performance, which has an impact on the environment in which employees work and carry out their activities, colleagues will always call. Keywords: Work Stress, Work Discipline, Employee Performance & OCB